Please mr panda - Antony Steve (London; Hodder Children's Books, 2017)
Panda has a tray of doughnuts. Animal after animal tells him the one they want, but it's only when Lemur says 'please' politely that Panda will give any out! A witty and stylish lesson that manners will get you everything. Even a trayload of doughnuts.